Comparing the Perception of Patterns of Aging in Adolescents and Young Adults Based on Grounded Theory - Mohammad Kahrobaei Kalkhuran Alya; Javad Changi Ashtiani; Abdollah Motamedi (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives The current study was conducted to compare the perceptions of aging between young and adolescent individuals. The perception of aging is defined as the individual's perception of one's aging in their socio-cultural context. This concept subsumes all aspects of consciousness, perception, experience, assessment, interpretation, and cognition related to the process of aging. Methods & Materials This qualitative study was carried out according to the grounded theory methods in 2019 in Tehran, Iran. A total of 20 young (10 males) and 17 adolescent (8 females) participants were selected by purposive sampling, and the data were collected through semi-structured interviews until data saturation was reached.  Results 121 concepts were selected, of which 83 were from interviews with adolescents and 37 from the young. After analysis and categorization of concepts, 32 subcategories were found, including 18 related to adolescents and 14 related to the young, and 5 main categories, with 3 and 2 categories   related to adolescents and the young. Conclusion In comparing the pattern of perception of old age in adolescents and young people, although in terms of frequency and semantic diversity of categories, slight differences are observed in these two groups in terms of the process of formation and movement of the final pattern, no distinction is seen between the two groups.